ANALYSIS OF DOMESTIC DRINKING WATER USE BEKASI CITY, WEST JAVA, INDONESIA - Rahman, Akhmad Taufiqur; Ardiatma, Dodit; Ilyas, Nurilman (Journal of Environmental Engineering and Sustainable Technology, 2024)
The purpose of this study is to determine the latest average value of domestic drinking water usage in Bekasi City and analyze the factors that influence changes in the average use of domestic drinking water in Bekasi City. This type of research is quantitative research with linear regression analysis. Data collection was carried out by distributing questionnaires and interviews. The population of Bekasi City is 3,075,690 people, with a sample size of 320 respondents. The results showed that the Income variable had an effect on the Domestic Drinking Water Use variable in Bekasi City, with a significance value of 0.00 <0.05 and a calculated t value of 6.144 <12.71. The Higher Education Level variable affects the Domestic Drinking Water Use variable in Bekasi City, with a significance value of 0.021> 0.05 and a calculated t-value of 2.357 < 12.71. The Decent Housing variable affects the Domestic Drinking Water Use variable in Bekasi City, with a significance value of 0.022 <0.05 and a calculated t-value of 3.180 <12.71. The averages value of domestic drinking water usage in the latest Bekasi City is 243.093 liters/person/day in 2024.